Effect of organic manures, inorganic fertilizers and biofertilizers on the nutrient concentration in leaves at different growth stages of banana cv Poovan. - K. Manivannan, P. Selvamani, (Journal of Phytology, 2009)
<span style="font-size: 10pt; font-family: ";Bookman Old Style";,";serif";; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Banana (Musa spp) and plantain are known for their antiquity and are interwoven with Indian heritage and culture and it Ã‚Â is one of the most important fruits grownÃ‚Â and consumed worldwide. Ã‚Â Ã‚Â A field experiment was laid out in randamised block designÃ‚Â with ten treatments and three replications consisting recommend dose of fertilizers (RDF) Ã‚Â and RDF combinedÃ‚Â withÃ‚Â Ã‚Â organic Ã‚Â Ã‚Â manures( Farm yard manure, Vermicompost andÃ‚Â Neem cake) and bioferlizers (VAM, azospirillum, PSB,Ã‚Â T. harizianum) at different combinationsÃ‚Â to know their nutrient concentrationÃ‚Â in banana leaves and soil at different growth periods viz., vegetative stage, flowering stage and harvesting stage. Sample preparation was performed with closed vassal microwave digestion. The major and micronutrients were analysed using the ICP-OES (Optima 2000). E-Merck multi-elemental standard used as a reference standard and ultra pure 2% HNO3 was applied as an internal standard. Ã‚Â T8 Ã‚Â treatment(50 per cent Ã‚Â RDF through inorganic fertilizers Ã‚Â ,organic manures with bio ferlizers) recorded significantly highest leafÃ‚Â nitrogen and potassiumÃ‚Â (3.24Ã‚Â amd 0.44%) during vegetative stage, flowering (3.58%) and Ã‚Â harvesting stages(2.68 %) than untreated plants Ã‚Â T1(2.02,2.12 and 1.51%). Highest Ã‚Â Leaf phosphorus (0.42,0.43 and 0.38 %), sodium(0.40, 0.44 and 0.32)Ã‚Â magnesium(1.61.1.81, and 0.81 %). Significantly lowest concentration was found in untreated plants. The highest micro nutrients were noted in T8 followed by Ã‚Â Ã‚Â T10 treatment in all the stages.